Perbedaan Pengaruh Latihan Boomerang Run With The Ball dengan Latihan Curving Line Trajectory Terhadap Kecepatan Menggiring Bola dalam Permainan Sepakbola pada Siswa Usia 16 Tahun Sekolah Sepakbola (SSB) Tunas Muda Rantau Prapat Tahun 2021 - Abady, Andi Nur; Siregar, Fajar Sidik; Siregar, Arifin (Journal of Technology and Literacy in Education, 2022)
This study aims to find out which is the greater effect between boomerang run with the ball exercise and curving line trajectory exercise on dribbling speed in 16 year old students of Tunas Muda Rantau Prapat soccer school (SSB) in 2021. The population of SSB Tunas Muda students is 42 people. In this study, 18 year old students from Tunas Muda Rantau Prapat Soccer School (SSB) were enrolled. The number of samples of 16 people was obtained by random sampling technique. The method used in this research is the experimental method. The research instrument for data collection with tests and measurements is a soccer dribbling speed test, to determine the athlete’s soccer dribbling speed. Furthermore, they were divided into two groups using the matching pairing technique, namely the boomerang run with the ball training group and the curving line trajectory training group. The study was conducted for 6 (six) weeks with exercise 4 (four) times a week. The analysis of the first hypothesis can be concluded that there is a significant effect of the boomerang run with bhe ball exercise on the speed of dribbling in soccer games for 16-year-old students of Tunas Muda Rantau Prapat football school (SSB) in 2021. The analysis of the second hypothesis can be concluded that there is a significant effect of curving line trajectory training on the speed of dribbling in soccer games for 16 year old students of Tunas Muda Rantau Prapat football school (SSB) in 2021. Analysis of the third hypothesis can be concluded that the boomerang run with the ball exercise has a greater effect than the curving-line trajectory exercise on the speed of dribbling in soccer games for 16-year-old students of Tunas Muda Rantau Prapat football school (SSB) in 2021. Keywords: boomerang run with the ball, curving line trajectory,dribbling